Therapeutic, Prophylactic, and Functional Use of Probiotics: A Current Perspective - Aponte, Maria; Murru, Nicoletta; Shoukat, Mahtab (Frontiers in Microbiology, 2020)
PProbiotics are considered as 21st century panpharmacon due to their competent remedial power to cure from gastrointestinal dysbiosis, systematic metabolic diseases, and genetic impairments up to complicated neurodegenerative disorders. It paved way for an innovative managing of various severe diseases through palatable food products. Probiotics role as a “Bio-Therapy” increased its significance in food and medicine due to many competitive advantages over traditional treatment therapies. Probiotics’ prophylactic and therapeutic potential has been assessed through hundreds of pre-clinical and clinical studies. In addition, food industry employs probiotics as functional and nutraceutical ingredients to enhance the added value of food product in terms of increased health benefits. However, regardless of promising health boosting effects, probiotics efficacy still needs an in-depth understanding of systematic mechanisms and factors supporting the healthy actions.